PRL3-zumab as an immunotherapy to inhibit tumors expressing PRL3 oncoprotein - Min Thura (Nature Portfolio, 2019)
Phosphatase of regenerating liver 3 (PRL3) is usually found intracellularly, and is over-expressed in cancer cells. Here the authors show that PRL-3 is also detectable on cell surface, and can be recognized by PRL3-zumab to recruit immune cells into tumor to promote anti-tumor immunity, thereby implicating PRL-3 as a potential tumor antigen.